Burden of AIDS in a Brazilian State - Helena Caetano Gonçalves e Silva; Jane da Silva; Jefferson Traebert (Elsevier, 2014)
Summary: Background: To estimate the burden of a disease implies the simultaneous quantification of the impact of early mortality and the health problems that affect the individual's quality of life, and this evaluation can be particularly important in a disease such as AIDS that has become a long-term disease. The purpose of this study was to determine the burden of disease due to AIDS in the Brazilian Southern State of Santa Catarina. Methods: An ecological designed study was performed using death and AIDS notifications data for 2009. The disability adjusted life years (DALYs) were estimated by the sum of years of life lost (YLL) and the years lived with disability (YLD). The YLL was estimated as the difference between the life expectancy from birth and the age at death with the application of a discount rate of 3% per year. The YLD was estimated as the product of the Burden of Disease Study's weight for AIDS of 0.167 and its average duration of 108 months in Brazil for the incident cases. The YLL, YLD and DALY rates were calculated per 100,000 inhabitants by sex and age groups. Results: There were 2034 notified cases and 689 deaths due to AIDS reported. There were 15,756.5 YLLs estimated, resulting in 257.5 YLLs/100,000 inhabitants, and 4554.1 YLDs were estimated, resulting in 74.4 YLDs/100,000 inhabitants. The DALY was estimated at 20,310.6, with a rate of 331.9 DALYs/100,000 inhabitants. The highest rates were observed in males in the age groups 30-44 and 45-59 years. Conclusions: The burden of AIDS was high and was observed mainly in adults, with a predominance in males. Keywords: Measurements in epidemiology, Acquired immunodeficiency syndrome, Basic indicators for health, Burden of disease